Unravelling the complex story of intergenomic recombination in ABB allotriploid bananas - Cenci, Alberto; Sardos, Julie; Hueber, Yann; Martin, Guillaume; Breton, Catherine; Roux, Nicolas Stephan M.; Swennen, Rony L.; Carpentier, Sebastien C.; Rouard, Mathieu (Oxford University Press, 2021)
• Background and Aims Bananas (Musa spp.) are a major staple food for hundreds of millions of people in developing countries. The cultivated varieties are seedless and parthenocarpic clones of which the ancestral origin remains to be clarified. The most important cultivars are triploids with an AAA, AAB or ABB genome constitution, with A and B genomes provided by M. acuminata and M. balbisiana, respectively. Previous studies suggested that inter-genome recombinations were relatively common in banana cultivars and that triploids were more likely to have passed through an intermediate hybrid. In this study, we investigated the chromosome structure within the ABB group, composed of starchy cooking bananas that play an important role in food security. • Methods Using SNP markers called from RADSeq data, we studied the chromosome structure of 36 ABB genotypes spanning defined taxonomic subgroups. To complement our understanding, we searched for similar events within nine AB hybrid genotypes. • Key Results Recurrent homologous exchanges (HEs), i.e. chromatin exchanges between A and B subgenomes, were unravelled with at least nine founding events (HE patterns) at the origin of ABB bananas prior to clonal diversification. Two independent founding events were found for Pisang Awak genotypes. Two HE patterns, corresponding to genotypes Pelipita and Klue Teparod, show an over-representation of B genome contribution. Three HE patterns mainly found in Indian accessions shared some recombined regions and two additional patterns did not correspond to any known subgroups. • Conclusions The discovery of the nine founding events allowed an investigation of the possible routes that led to the creation of the different subgroups, which resulted in new hypotheses. Based on our observations, we suggest different routes that gave rise to the current diversity in the ABB cultivars, routes involving primary AB hybrids, routes leading to shared HEs and routes leading to a B excess ratio. Genetic fluxes took place between M. acuminata and M. balbisiana, particularly in India, where these unbalanced AB hybrids and ABB allotriploids originated, and where cultivated M. balbisiana are abundant. The result of this study clarifies the classification of ABB cultivars, possibly leading to the revision of the classification of this subgroup.